1999
DOI: 10.1161/01.res.85.5.415
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular [Ca 2+ ] i Gradients During Excitation-Contraction Coupling in Newborn Rabbit Ventricular Myocytes

Abstract: The central role of T-tubule and sarcoplasmic reticulum (SR) diadic junctions in excitation-contraction (EC) coupling in adult (AD) ventricular myocytes suggests that their absence in newborn (NB) cells may manifest as an altered EC coupling phenotype. We used confocal microscopy to compare fluo-3 [Ca2+]i transients in the subsarcolemmal space and cell center of field-stimulated NB and AD rabbit ventricular myocytes. Peak systolic [Ca2+]i occurred sooner and was higher in the subsarcolemmal space compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
127
3
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(152 citation statements)
references
References 33 publications
19
127
3
1
Order By: Relevance
“…In adult, Kir6.2 and SUR2 subunits both are expressed at the sarco- lemma as well as in sarcomeric striated patterns, which we previously attributed to high expression levels of these subunits in t-tubular structures (22). Our observation of predominantly surface expression of Kir6.2 subunits in immature ventricular myocytes is entirely consistent with the fact that neonatal myocytes largely lack t-tubules (30,31). However, we still observe diffuse intracellular staining with the SUR2 antibodies used.…”
Section: Discussionsupporting
confidence: 89%
“…In adult, Kir6.2 and SUR2 subunits both are expressed at the sarco- lemma as well as in sarcomeric striated patterns, which we previously attributed to high expression levels of these subunits in t-tubular structures (22). Our observation of predominantly surface expression of Kir6.2 subunits in immature ventricular myocytes is entirely consistent with the fact that neonatal myocytes largely lack t-tubules (30,31). However, we still observe diffuse intracellular staining with the SUR2 antibodies used.…”
Section: Discussionsupporting
confidence: 89%
“…causes significant changes in the Ca 2ϩ transient. In addition, the sodium-calcium exchanger has been shown to be larger in newborn rabbit ventricle than adults and may act, in ventricular cells, in the reverse mode to bring Ca 2ϩ into the cell during the plateau of the action potential and thus may be able to act as a trigger SR Ca 2ϩ release (25)(26)(27)(28). Reverse-mode sodiumcalcium exchanger as a trigger for calcium release has been shown in cardiac myocytes from several species (29 -31).…”
Section: Discussionmentioning
confidence: 99%
“…Seki et al recently observed a significant reduction in the magnitude of Ca 2+ transients in fetal rat myocytes induced by thapsigargin, 23 whereas Haddock et al reported that no Ca 2+ transients in neonatal rabbit ventricular myocytes are inhibited following the addition of thapsigargin. 28 These conflicting findings may be due to differences in methodology and animal species used. It has been reported that cultured myocytes from neonatal rats exhibit an apparent reduction of RyR density, and Ca 2+ signaling during E-C coupling is modified.…”
Section: Contribution Of Serca To Relaxation In Fetal Ventricular Heartmentioning
confidence: 99%